2018
DOI: 10.1002/mame.201700596
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Latex Containing Polyelectrolyte Multilayers

Abstract: Self‐healing paints would have the potential benefit of protecting the underlying substrate and extending the coating's service life. As a step toward those types of coatings, this work examines layer‐by‐layer films of branched poly(ethylene imine)/poly(acrylic acid) with the inclusion of various types of latex particles with different Tg and different compositions. Due to high mobility of the polyelectrolyte chains when plasticized with water, water enabled self‐healing of these films is demonstrated, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Self‐healing polymers with the capability to repair internal cracks or external fractures by themselves have been developed over the past decades . Once the polymer is healed, the conductive network will be healed subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐healing polymers with the capability to repair internal cracks or external fractures by themselves have been developed over the past decades . Once the polymer is healed, the conductive network will be healed subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Patterns printed in functional materials on length scales varying from micrometers to millimeters are utilized in cell culture, tissue engineering, optics, interactions in percolation transitions. From the practical standpoint, aqueous latex NP dispersions can be used for the preparation of films and coatings from both hydrophilic and hydrophobic polymers, [20][21][22][23] with applications as paints, [24] films for biometrics and optical data storage, [25][26][27][28] self-healing coatings, [29] and membranes. [30] Importantly, in such systems, high molecular weight polymers can be used without increase in dispersion viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to change independently the dimensions, charge, surface chemistry, and functionality of polymer latex NPs makes them promising building blocks of nanocolloidal gels, as it enables systematic studies of the role of interparticle interactions in percolation transitions. From the practical standpoint, aqueous latex NP dispersions can be used for the preparation of films and coatings from both hydrophilic and hydrophobic polymers, [ 20–23 ] with applications as paints, [ 24 ] films for biometrics and optical data storage, [ 25–28 ] self‐healing coatings, [ 29 ] and membranes. [ 30 ] Importantly, in such systems, high molecular weight polymers can be used without increase in dispersion viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Hoffman et al prepared PEMUs with blended polyelectrolytes that yielded improved anion separation and salt rejection . Cui et al demonstrated self-healing properties of PEMUs blended with latex nanoparticles, while Duan et al showed that graphene oxide (negatively charged) added to a PEC enhanced the mechanical properties of the complex . The elastic modulus of blended polyelectrolytes varies strongly with the blend composition .…”
Section: Introductionmentioning
confidence: 99%